2017
DOI: 10.1016/j.ultras.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic ultrasonic vibration amplitude model during rotary ultrasonic machining of CFRP composites

Abstract: Rotary ultrasonic machining (RUM) has been investigated in machining of brittle, ductile, as well as composite materials. Ultrasonic vibration amplitude, as one of the most important input variables, affects almost all the output variables in RUM. Numerous investigations on measuring ultrasonic vibration amplitude without RUM machining have been reported. In recent years, ultrasonic vibration amplitude measurement with RUM of ductile materials has been investigated. It is found that the ultrasonic vibration am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A possible explanation of this behavior can be linked with the heat accumulation when drilling CFRP under dry cutting mode. CFRP material has generally low thermal conductivity and low heat capacity; as a result heat can be easily generated and accumulate in the cutting zone [47]. Literature [48] points out that glass transition temperature of CFRP is around 160-200°C.…”
Section: Effect Of Lubrication Methodsmentioning
confidence: 99%
“…A possible explanation of this behavior can be linked with the heat accumulation when drilling CFRP under dry cutting mode. CFRP material has generally low thermal conductivity and low heat capacity; as a result heat can be easily generated and accumulate in the cutting zone [47]. Literature [48] points out that glass transition temperature of CFRP is around 160-200°C.…”
Section: Effect Of Lubrication Methodsmentioning
confidence: 99%
“…So we concluded that most of the researcher have focused on material removal along with some researchers have coted some material with magnetic abrasive particle as wire magnetic and induction free abrasive wire sawing (MIFAWS) is one of the method by which Chunyan Yao et al have prepared magnetic abrasive particle layer on the wire surface and then thickness was calculated for to find out how much magnetic Process was analyzed by MATLAB and results are discussed in detail for developing new areas of research [1]. The model used for machining is thermo-physical [24,25,26], electro-mechanical and thermo-electrical [27,28,29,30]. EDM and WEDM process is used for some complicated and tough to machine work pieces and for these machines the numerical model is created to analyses the process parameters for optimization [4,6,14,17], and for semi observational data [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an advanced machining technology, the ultrasonic vibration assisted sawing is widely used to machine hard-brittle materials [18,19,20,21]. It not only improves the surface quality after machining, but also increases the machining efficiency [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%